Syntetyczny model efektywności łańcucha dostaw - Kot, Sebastian (The Comprehensive Model of the Supply Chain Effectiveness, 2005)
In the paper author presents an overview of literature on supply chain effectiveness analysis. There are chosen effectiveness methods and discussion of their usage. Finally the comprehensive model of the supply chain effectiveness analysis is proposed.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1078, s. 74-80